A high-fidelity simulator for needle cricothyroidotomy training is not associated with increased proficiency compared with conventional simulators: A randomized controlled study. Issue 8 (February 2019) - Katayama, Atsuko; Nakazawa, Harumasa; Tokumine, Joho; Lefor, Alan Kawarai; Watanabe, Kunitaro; Asao, Takayuki; Yorozu, Tomoko
Abstract: Background: A high-fidelity task simulator for cricothyroidotomy was created using data from a 3-dimensional (3D) computed tomography scan using a 3D printer. We hypothesized that this high-fidelity cricothyroidotomy simulator results in increased proficiency for needle cricothyroidotomy compared with conventional simulators. Methods: Cricothyroidotomy-naive residents were recruited and randomly assigned to 2 groups, including simulation training with a conventional simulator (Group C) and with a high-fidelity simulator (Group 3D). After simulation training, participants performed cricothyroidotomy using an ex vivo porcine larynx fitted with an endoscope to record the procedure. The primary outcomes were success rate and procedure time. The secondary outcome was a subjective measure of the similarity of the simulator to the porcine larynx. Results: Fifty-two residents participated in the study (Group C: n = 27, Group 3D: n = 25). There was no significant difference in the success rate or procedure time between the 2 groups (success rate: P  = .24, procedure time: P  = .34). There was no significant difference in the similarity of the simulators to the porcine larynx ( P  = .81). Conclusion: We developed a high-fidelity simulator for cricothyroidotomy from 3D computed tomography data using a 3D printer. This anatomically high-fidelity simulator did not have any advantages compared with conventional dry simulators.